2020
DOI: 10.1371/journal.pone.0230589
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility, and repeatability of corneal topography measured by Revo NX, Galilei G6 and Casia 2 in normal eyes

Abstract: PurposeTo test the repeatability and reproducibility of the topography module in posterior segment spectral domain optical coherence tomography with Revo NX (new device) and to compare keratometry values obtained by a Scheimpflug tomography (Galilei G6) and a swept source OCT (Casia 2). MethodsIn this prospective study, healthy subjects with nonoperated eyes had their central corneal thickness (CCT), anterior and posterior K1/K2 corneal power measured with the new device. Two operators made 6 measurements on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 23 publications
0
38
1
Order By: Relevance
“…Considering that the 0.5 D is the currently used IOL power step, the total keratometry values derived from each device should not be interchanged when calculating IOLs. The discrepancy of the three devices in total keratometry could be caused by the different algorism for calculating total keratometry in each device [5,8,19]. IOLMaster 700 obtains anterior keratometry with 18 reflected spots in hexagonal patterns at three zones (1.5 mm, 2.5 mm, and 3.5 mm) and posterior keratometry with SS-OCT tomography [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the 0.5 D is the currently used IOL power step, the total keratometry values derived from each device should not be interchanged when calculating IOLs. The discrepancy of the three devices in total keratometry could be caused by the different algorism for calculating total keratometry in each device [5,8,19]. IOLMaster 700 obtains anterior keratometry with 18 reflected spots in hexagonal patterns at three zones (1.5 mm, 2.5 mm, and 3.5 mm) and posterior keratometry with SS-OCT tomography [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Wylegala et al reported a CR of anterior and posterior corneal power (in two meridians) with a spectral domain OCT (Revo NX) to be 0.33-0.46 and 0.10-0.11, respectively. 24 One study reported a CR with the Pentacam for K1/K2 and astigmatism to be 0.07 and 0.39-0.44, respectively, for both SimK and TCP, and 0.11 and 0.12, respectively, for PCP. 43 Another study found that repeatability was worse for anterior elevation but better for posterior elevation with the Casia compared to the Pentacam.…”
Section: Discussionmentioning
confidence: 99%
“…While combined systems offer lower price and higher resolution due to shorter wavelength of light, the lack of collimated light at the cornea makes the measurements distance-dependent. 24 Dedicated AS systems offers better tissue penetration and imaging depth due to of higher wavelength of light, and also larger measurement diameter. 24,25 The aim of this study was to compare the repeatability of keratometry between different instruments in patients with a hyperosmolar tear film and a control group of patients with a normal tear film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown lower repeatability of OCT-based keratometry compared to reflectometry or Scheimpflug-based keratometry. 26–29 …”
Section: Introductionmentioning
confidence: 99%